The Concept Of Mosque Management Based On Hadith Perspective - Filah, Nafilah; Junengsih, Junengsih (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
The concept of mosque management is an important aspect in managing and maintaining the function and role of the mosque as a center of worship and religious activities. This study explores a number of hadiths relevant to mosque management that can be found in various hadith books. This research uses a qualitative approach and applies a thematic method, namely by collecting hadith from various books according to certain themes. In addition, this study aims to provide a more specific explanation of how these hadiths can be applied in the context of mosque management in the modern era. Analysis of these hadiths can help mosque administrators, imams, and Muslim communities in developing more effective strategies to run and manage mosques well. In the results of this study, the author revealed that there are several hadiths that can provide guidance on various aspects, such as mosque financial management, religious program planning, community empowerment, relations with worshippers and can be interpreted in a social, technological context that continues to develop in the modern era. Through this approach, this research seeks to provide deep and contextual insights into mosque management based on hadith teachings, so that mosques can continue to be relevant and effective centers of religious and spiritual activity in meeting the needs of modern Muslim communities.